The Role Of Service And Product Quality on Customer Satisfaction At PT Iwatani Industrial Gas Indonesia, Cikupa Tangerang Marketing Area - Chasanah, Uswatun; Triyono, Agus; Hayati, Feb Amni (Jurnal Akuntansi, Manajemen dan Ekonomi, 2022)
Product, price, promotion, place, people, and physical evidence are vital parts of product marketing strategy planning provide a basis for companies to take adequate steps to maintain customer satisfaction. The research aims to specifically look at the role of service quality and product quality to increase customer satisfaction at PT Iwatani Industrial Gas Indonesia Marketing Area Tangerang. The final sample was set at 111 company customers. Analysis of the data using multiple linear regression analysis technique that begins with the instrument quality test and the classical assumption test. The conclusion of the research aims to specifically look at the role of service quality and product quality to increase customer satisfaction significantly impacts the test results simultaneously with a contribution of 75.7 percent. Still, in partial testing, only product quality factors have a role in increasing customer satisfaction at PT Iwatani Industrial Gas Indonesia Marketing Area Tangerang